Variation in epiphytic vegetation in spruce plantations and adjacent native birch forests in North Norway - Nilsen, Kjersti Wannebo (Universitetet i Tromsø, 2007)
Epiphytic vegetation can contribute to increased knowledge on how planting of spruce in areas where spruce does not occur naturally in the landscape can affect the environment. In the current study, 31 spruce plantations in Troms and Vesterålen in North Norway were investigated, with emphasis on species abundance of macrolichens on tree trunks and branches. The main assumption was that planting of spruce affects the communities of epiphytic vegetation. Sixty-two species/groups of epiphytic vegetation were recorded. Detrended Correspondance Analysis (DCA) and Canonical Correspondence Analysis (CCA) ordination methods displayed prominent differences in species composition between spruce, birch and transition quadrates. Species diversity, species numbers and variance were significantly lower in spruce plantations than in native birch forest. Seventeen major environmental variables were significantly related to the community differences. The variation from coast to inland, differences in temperature and altitude, as well as distance to humid sources is the main regional factors that best explain the variation incommunity structures. In addition, local differences such as various tree characteristics, presence of other tree species, and bark pH also contribute to explaining variation within and between spruce and birch quadrates. As spruce plantations in North Norway mature, these can provide habitats for more rare, shade-tolerant and/ or thermophilous species, as observed in this study. However, plantations do not have a positive effect on the epiphytic biodiversity locally, which in terms may affect other levels of the ecosystem. Investigations on the consequences of spruce planting on the biodiversity in northern birch forests are important to the future planning of new plantations. Habitat-rich areas should not be used for plantations. Moreover, management of plantations, such as selective cutting and thinning, should be attempted in order to enhance species richness and biodiversity within plantations.